Student-Centered Learning Communities: Teachers' Perspectives - Ardeth Deay; Joy Faini Saab (Journal of Research in Rural Education, 1994)
This study was designed to examine teachers' perceptions ofchanges in their classroom practices that have occurred as a result oftraining in process-education techniques commonly described as the Foxfire approach to learning. Teachers participated in a university class during which they studied techniques for implementing experiential, student-centered instructional approaches that give students a voice in the process oftheir education. Changes in classroom practices that affect teachers' interactions with students, parents, and other community members are described.